2015
DOI: 10.1007/s12544-015-0167-3
|View full text |Cite
|
Sign up to set email alerts
|

A Data Envelopment Analysis approach for accessibility measures: Simulating operational enhancement scenarios for railway across Europe

Abstract: Introduction As well known, infrastructure endowment influences competitiveness of a region since the characteristics of a transport system in terms of capacity, connectivity, speeds, etc. determine the advantages/disadvantages of an area compared to other locations. This article attempts to investigate the potential impacts on rail accessibility across Europe when different possible operational enhancement scenarios are simulated. Methods The simulations are carried out by means of a combination of the TRANST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Machine learning approaches offer a wide range of metrics to estimate model precision, as well as tools for the interpretation of the results. A potential disadvantage of such approaches stems from the nature of the issue to be analyzed: the large number of non-linear tree-like decisions may obscure the physical interpretation of the resulting model [42,43]. Additionally, unless a suitable validation strategy is in place, models that overfit with respect to their underlying data may not generalize well when applied to new data.…”
Section: Methodsmentioning
confidence: 99%
“…Machine learning approaches offer a wide range of metrics to estimate model precision, as well as tools for the interpretation of the results. A potential disadvantage of such approaches stems from the nature of the issue to be analyzed: the large number of non-linear tree-like decisions may obscure the physical interpretation of the resulting model [42,43]. Additionally, unless a suitable validation strategy is in place, models that overfit with respect to their underlying data may not generalize well when applied to new data.…”
Section: Methodsmentioning
confidence: 99%
“…Rotoli et al (2015) [17] followed a Data Envelopment Analysis approach to estimate the benefits at regional level from increased accessibility and suggested a positive correlation. Rokicki et al (2018) [18] identified a weak-but positive-correlation between accessibility and regional employment.…”
Section: Accessibility Analysis and Border Regionsmentioning
confidence: 99%
“…This indicator should be interpreted from an economic perspective, as it measures the economic potential of each place considered and the changes to be caused by new infrastructure (Gutierrez, 2001) [29]. The formulation used here follows Condeço-Melhorado et al (2017) [21] and Rotoli et al (2015) [22], and applies a parameter a = 1, which corresponds to a linear decay function. While other, higher, values can be considered, the spatial delimitation of the area of interest in this specific application makes this selection non-critical (as Stępniak & Rosik, 2018 [4] also suggest).…”
Section: Potential Accessibilitymentioning
confidence: 99%
“…In order to recognize changes in the efficiency and productivity of railway freight transportation in Europe, [119] applied DEA to analyze different European countries from 1980 to 2003.…”
Section: Data Envelopment Analysis (Dea)mentioning
confidence: 99%
“…Throughout the investigation of the potential impacts on rail accessibility across the Europe for different scenarios, in [119] the DEA method was employed. Working on the real-time optimization of train scheduling decisions at a complex railway network during congested traffic situations, [124] used DEA in evaluating the relative efficiency of the different optimization formulations.…”
Section: Data Envelopment Analysis (Dea)mentioning
confidence: 99%